Bioethics in tissue engineering: an Islamic perspective - Abdul Rahman, Rozlin; Che Ahmad, Aminudin; Abdul Rahman, Suzanah; Sha'ban, Munirah (2011)
Islam is not only a religion; it is a way of life. Islamic ethical guidelines of research are derived from the purposes and principles of the Islamic law (Sharia). Tampering with God's creation is clearly rejected in Islam. However in medical field, exception has been made when it comes to producing medicine or any other materials and methods that will improve suffering and eliminate diseases. The general purposes of tissue engineering are basically to facilitate organ transplant and to produce organs or tissues suitable for research intentions. Nevertheless, its reflection on bioethics in tissue engineering research are still insufficient and much attention is needed to provide the ulama' (Islamic scholar) and scientists with guidelines and safeguards for the benefit of all mankind. With continuous advancement in the development and scientific breakthrough in the field of biotechnology especially in tissue engineering, religion and ethical perspectives come hand in hand. Although it gives a ray of hope, the bright picture also generates some worries on issues as the assumption that it is utilizing a human being for the interests of somebody else and also the arguments on the origin of tissues. The presentation aims to discuss on the on-going debates within Islamic perspectives of the ethical issues related to tissue engineering research. It is hope that the outcome will encourage more allowable experimentation to explore this grey area from a standpoint of Islamic teaching as long as it is with the purpose of improving human health.